Pengaruh Latihan Menangkap Bola Dalam Menyelamatkan Bola Pada Penjaga Gawang Tim Futsal Patriot FC FKIP Unpatti - Kelwow, Abdul Latif; Matitaputty, Johanna (Prgram Studi Pendidikan Jasmani Kesehatan dan Rekreasi, FKIP Universitas Pattimura, 2024)
This research is a field experiment research with one group pre test and post test design. The sample in this study were all Patriot Fc futsal goalkeepers, totaling 10 players. The instrument used in this research is a test of the ability to save the ball, which aims to measure the reaction speed of the goalkeeper in saving the ball. In the t test that has been carried out above based on the average value and standard deviation that has been analyzed, the tcount is 7,943. As for the table is 2,262. Which means that tcount > ttable (7.943 > 2.262) then the alternative hypothesis (Ha). Based on the results of testing the hypothesis in this study, it was found that there was an effect of reaction speed training on the goalkeeper's ability to save the ball on the Patriot Fc futsal team, Physical Education and Research Program Fkip, Unpatti.